Ožívání městského společenství: Případ komunitních zahrad v Praze - Mikovcová, Markéta (Lidé města, 2015)
This paper empirically examines the role of community in the community gardens of Prague. The goal is to determine whether the community is truly established, and whether it influences the public space. The case study of community gardens in Prague was conducted using the methods of semi-structured interviews and participant observations. Since community gardens are on the rise as bottom-up initiatives which react to the degree of individualisation in the city, they could be comprehended also as an activation of civic society. Although community gardens mutually differ, every one of them influences their geographic and social space to some extent. Regardless the way they are organised, there is a developed in-group sense among the gardeners which confirms the existence of community. The fact that community gardens seek to develop the space they are located in and that they engage in activities with local entrepreneurs and civic associations, but also that they associate people with an interest in gardening who would have not met without the existence of community gardens, leads to the conclusion that they develop space-based communities as well as interest-based ones.